Field measurements and numerical analysis of the energy consumption of urban rail vehicle air-conditioning systems. (August 2020) - Wang, Honglin; Bi, Haiquan; Zhou, Yuanlong; Li, Ce
Highlights: Fresh air and passenger loads significantly affect energy performance of the system. The air-conditioning systems mainly switch between half cooling and ventilation. A temperature control strategy in car has a great influence on energy consumption. The proposed inverter control strategy led to energy savings. Field measurements were conducted in real urban rail vehicle operation in summer. Abstract: The air-conditioning systems (ACSs) of urban rail vehicles account for a large proportion of their total operating energy consumption. Measuring and analyzing this consumption is, therefore, extremely important for developing energy-saving strategies. In this study, field measurements were conducted during real urban rail vehicle operation in the summer, collecting data for parameters such as fresh air, actual car passenger, and solar radiation intensity. These data were used as an input to establish a numerical model of the ACS using AMESim. The energy performance was analyzed for the proportion of each load, the proportion of time spent in operation mode, various influencing factors, and the impact of control strategies. The results indicate that the fresh air and passenger loads account for 66% and 24% of the load, respectively, and that the ACSs switch between half-cooling and ventilation throughout most of the operating time. Compared to a fixed fresh air system, a control mode for a variable fresh air system enabled 14.5% energy savings. Compared to on-off air-conditioning control, the proposed inverter control strategy produced 14.0–31.5% energy savings. The study not only can provide a basis for formulating energy consumption specifications, but also contribute to develop an effective ACS control strategy.